Pine Webworm, Pococera robustella (Zeller) (Insecta: Lepidoptera: Pyralidae) - Albert E. Mayfield, III (EDIS, 2007)
EENY-408, a 3-page illustrated fact sheet by Albert E. Mayfield, III, is part of the Featured Creatures collection. It provides information about this common defoliator of pines in the eastern United States, its distribution, description, biology, hosts, damage, and management. Includes references. Published by the UF Department of Entomology and Nematology, May 2007.